Pengembangan Modul Gambar Teknik dan Listrik Berbantuan Software AutoCAD: Analisis Uji Validitas - Yoga Syafren Amanda; Hambali Hambali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
The lecture process is a communication process, where classroom activities are a separate world of communication, where lecturers and students interact with each other to achieve lecture goals. Lecturers, one of the main components in the lecture process, are able to create and create conditions and atmosphere that can stimulate students to learn actively and dynamically. The module is one of the tools that can be used by lecturers to deliver lecture material. Things that can affect lecture activities, namely the module as a tool in practical learning activities. The purpose of this research is to develop a module that is suitable for use so as to improve the quality of the practicum lecture process and increase students' understanding in mastering the lecture material. This type of research is Research and Development (R&D) with a 4D development model consisting of Define, Design, Develop, and Disseminate. The valid assessment of the module is carried out by experts consisting of media experts and material experts, the data collection instrument uses an assessment questionnaire. The results of this study obtained a module that can guide students to learn independently and guided based on media experts categorized as valid, while the feasibility of the material based on material experts get a valid category. So that the developed module can be used by lecturers to deliver lecture material in practicum.